PERSPECTIVES OF TRADITIONAL MARKET WOMEN ON EXCLUSIVE BREASTFEEDING IN THE WORKING AREA OF DELI TUA HEALTH CENTER WORK AREA YEAR 2023 - Yuki Nia Nadia Nahdeak; Ariani, Peny; Putri Ayu Yessy Ariescha (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Abstract One of the fundamental steps toward a healthy and productive life is breastfeeding, which is in line with the Sustainable Development Goals (SDGs) or Sustainable Development Goals 2030 (Bennett et al., 2020). Low rates of exclusive breastfeeding lead to various infant health problems. The North Sumatra Provincial Government has recorded 299 cases of infant mortality until July 2021. Records from the Ministry of Health of the Republic of Indonesia, as many as 31.36% of 37.94% of children are sick, because they do not receive exclusive breastfeeding. The prevalence of stunting in Indonesia is currently at 27.67%. The low coverage of exclusive breastfeeding is influenced by various obstacles to optimal breastfeeding, one of the biggest obstacles is working women, especially those who work in the informal sector. The purpose of this study was to determine